The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2023
DOI: 10.1111/jgh.16108
|View full text |Cite
|
Sign up to set email alerts
|

Risk of colorectal cancer after appendectomy: A systematic review and meta‐analysis

Abstract: Background and Aim Appendectomy is associated with various diseases, but whether it increases the risk of colorectal cancer (CRC) remains uncertain. We conducted a systematic review and meta‐analysis aimed at investigating the suggested correlation between appendectomy and CRC. Methods Systematic retrieval was performed using the PubMed, Embase, Cochrane library, Web of Science, and http://ClinicalTrials.gov databases up to May 4, 2022, for studies reported the influence of appendectomy on CRC, colon cancer (C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 47 publications
4
6
0
Order By: Relevance
“…A recent systematic review and meta‐analysis performed by Liu et al 15 . described findings similar to the trends described above, finding an overall OR of 1.31; 1.05–1.62 for CRC in the combined post‐appendectomy populations.…”
Section: Epidemiological Observation Of the Relationship Between Prev...supporting
confidence: 71%
See 1 more Smart Citation
“…A recent systematic review and meta‐analysis performed by Liu et al 15 . described findings similar to the trends described above, finding an overall OR of 1.31; 1.05–1.62 for CRC in the combined post‐appendectomy populations.…”
Section: Epidemiological Observation Of the Relationship Between Prev...supporting
confidence: 71%
“…A recent systematic review and meta-analysis performed by Liu et al 15 described findings similar to the trends described above, finding an overall OR of 1.31; 1.05-1.62 for CRC in the combined post-appendectomy populations. They further conducted a subgroup analysis based on geographical populations and concluded that the trend toward increased OR for CRC post-appendectomy was significant in American and Asian populations (OR 1.68; 1.15-2.44 and OR 1.46; 1.04-2.05, respectively), but not significant in European populations (OR 0.94; 0.87-1.02).…”
Section: Epidemiological Observation Of the Relationship Between Prev...supporting
confidence: 68%
“…Several studies have investigated the relationship between appendectomy and CRC risk, with some showing an increased risk of CRC after appendectomy, while others have either found no association or a potential protective effect. In a meta-analysis, individuals who had experienced an appendectomy had an elevated risk of CRC, implying a possible link with CRC development [ 7 ]. Conversely, a 14 years of follow-up large retrospective cohort study found that appendectomy patients had a 1.14 times higher risk of developing CRC than the general population [ 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…Considering the appendix's role in immune functions, it is essential to evaluate whether its presence or absence is linked to the development of other diseases, including colorectal cancer, inflammatory diseases, and infections [5]. The outcomes of previous studies in this area have been inconsistent [6][7][8][9][10][11]. Consequently, a comprehensive review study is needed to amalgamate these findings.…”
Section: Introductionmentioning
confidence: 99%